MODIFIKASI ALAT MEDIS STETOSKOP UNTUK MONITORING SUARA JANTUNG MENGGUNAKAN TAMPILAN GUI MATLAB - Irmawati, Dessy; Prasakti, Ridho (Elinvo (Electronics, Informatics, and Vocational Education), 2018)
Heart sounds are very important for the initial diagnosis of a disease. This article aims to modify the stethoscope's medical device by adding a Low Pass Filter (LPF) and a condenser sensor so that data can be recorded in a digital device. The stages of tool development begin with analysis, design, development and testing. At the analysis stage, it was stated that a conventional medical stethoscope can only be done by a medical expert directly, where data cannot be stored for detailed analysis purposes, the device is not equipped with LPF which can limit the frequency in a certain range, monitoring data can displayed in the Matlab GUI. The results of testing tools through functional tests indicate that the addition of LPF can reduce noise when retrieving heart sound data and data can be monitored through the Matlab GUI display. The results of the development of this tool are expected to improve accuracy in diagnosing heart sound abnormalities through monitoring data on the Matlab GUI display.